EVALUASI YIELD PRODUK TERHADAP FIX COST DAN VARIABLE COST PADA CAIRAN INFUS RINGER LACTATE - Adi Suroso; Amelia Lorensia; Abdul Rahem (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
The need for quality drugs can affect the price of drugs, because there were many requirement in the manufacturing process as stated in the GMP standard. On the other hand, the price of the COGS (before production) standard and COGS varian (after production) can be different due to changes in the values of factory over head (fixed cost and variable cost). So that it requires an analysis of COGS standard and variant. This study aims to analyze the differences in the COGS variant of Ringer Lactate infusion products to COGS standard. COGS variant value was calculated based on the yield of 30 batches. Descriptive analysis was performed for (1) Value (%) of COGS standard (2) Differences in value of variable cost and fixed cost of COGS variant to COGS standard, (3) COGS standard and variant. The results showed (1) COGS standard consist of raw materials (6.70%), packaging materials (49.58%), factory over head with variable costs (25.80%) and Fixed costs (18.00%); (2) The average yield of 30 batches was 94.947% and this causes in differences in variable cost of COGS variant - standard 4.422% and the differences in fixed cost of COGS variant – COGS standard 3,958% (3) There was 4,201 % differences in COGS variant to standard. Product yield influences the value of variable cost and fixed cost of COGS variants, causing a gap to the COGS standard. So that this gap should considered in setting the COGS standard.